2020
DOI: 10.20944/preprints202011.0402.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From m<sup>6</sup>A to Cap-Adjacent m<sup>6</sup>Am and Their Effects on mRNAs

Abstract: Although RNA modifications were discovered decades ago, the identification of enzymes that write, read, and erase RNA modifications enabled their functional study and spawned the field of epitranscriptomics. Coupling that knowledge to new methods has enabled the precise pinpointing of epitranscriptomic modifications across the transcriptome plus the elucidation of their functional consequences. PCIF1 (Phosphorylated CTD Interacting Factor 1) was shown to add N6, 2&rsquo;-O-dimethyladenosine (m6Am) marks at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 144 publications
(392 reference statements)
0
1
0
Order By: Relevance
“…Studies have demonstrated that mRNA with Cap 1 generally yields higher protein levels compared to Cap 0, although no distinct advantages have been established in comparison to Cap 2. Therefore, the choice of cap modification depends on the particular cell line or cellular environment in which the mRNA is to be delivered [27,28]. Another important function of the cap is to protect mRNA from degradation by 5'-end RNases, such as the XRN1 family [29].…”
Section: ′ Cap Structurementioning
confidence: 99%
“…Studies have demonstrated that mRNA with Cap 1 generally yields higher protein levels compared to Cap 0, although no distinct advantages have been established in comparison to Cap 2. Therefore, the choice of cap modification depends on the particular cell line or cellular environment in which the mRNA is to be delivered [27,28]. Another important function of the cap is to protect mRNA from degradation by 5'-end RNases, such as the XRN1 family [29].…”
Section: ′ Cap Structurementioning
confidence: 99%